Factors preventing materno-fetal transmission of SARS-CoV-2. (August 2020) - Celik, Onder; Saglam, Aylin; Baysal, Bora; Derwig, Iris E.; Celik, Nilufer; Ak, Mehmet; Aslan, Selma N.; Ulas, Mustafa; Ersahin, Aynur; Tayyar, Ahter T.; Duran, Bulent; Aydin, Suleyman
Abstract: Although many pregnant women have been infected by coronavirus, the presence of intrauterine vertical transmission has not been conclusively reported yet. What prevents this highly contagious virus from reaching the fetus? Is it only the presence of a strong placental barrier, or is it the natural absence of the some receptor that the viruses use for transmission? We, therefore, need to comprehensively understand the mechanism of action of the mammalian epithelial barriers located in two different organs with functional similarity. The barriers selected as potential targets by SARS-CoV-2 are the alveolo-capillary barrier (ACB), and the syncytio-capillary barrier (SCB). Caveolae are omega-shaped structures located on the cell membrane. They consist of caveolin-1 protein (Cav-1) and are involved in the internalisation of some viruses. By activating leukocytes and nuclear factor-κB, Cav-1 initiates inflammatory reactions. The presence of more than one Cav-1 binding sites on coronavirus is an important finding supporting the possible relationship between SARS-CoV-2-mediated lung injury. While the ACB cells express Cav-1 there is no caveolin expression in syncytiotrophoblasts. In this short review, we will try to explain our hypothesis that the lack of caveolin expression in the SCB is one of the most important physiological mechanisms that prevents vertical transmission of SARS-CoV-2. Since the physiological Cav-1 deficiency appears to prevent acute cell damage treatment algorithms could potentially be developed to block this pathway in the non-pregnant population affected by SARS-CoV-2. Highlights: Syncytiotrophoblasts do not express caveolin. SARS-CoV-2 does not bind to syncytiotrophoblasts. Placental barrier does not allow passage of SARS-CoV-2.